How do wound care nurses structure the subjective frame on palliative wound care? A Q-methodology approach - Ye-Na Lee; Sung Ok Chang (BMC Nursing, 2022)
Abstract Background Palliative wound care is important for stability in terminal care. It addresses both the physical and psychological needs of patients and facilitates other aspects of terminal care. Appropriate competencies of nurses regarding palliative wound care can improve patient outcomes and raise their quality of life. The purpose of this study was to identify how wound care nurses structure the subjective frames regarding palliative wound care. Method This study utilized Q-methodology to analyze their subjective viewpoints. Forty nurses experienced in palliative wound care were asked to completely classify 35 Q-statements into a normal distribution shape. The PQ-Method program was used to conduct principal factor analysis and varimax rotation for data analysis. Results This study revealed 4 Q-factors of palliative wound care: “Focusing on care within the boundary of current patient demands,” “Comparing continuously the priorities on wound healing and disease care,” “Preparing and preventing from worsening via tracking care in advance,” and “Moving forward with a clear direction by confronting the declining condition.” Conclusion We hope that the results of this study are used in the development of nursing education that reflects professional perspectives of palliative wound care, thus helping to improve nursing competencies in palliative care.